2004
DOI: 10.1111/j.1365-313x.2004.02271.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the proteins targeted by CDSP32, a plastidic thioredoxin participating in oxidative stress responses

Abstract: SummaryThe chloroplastic drought-induced stress protein of 32 kDa (CDSP32) is a thioredoxin induced by environmental stress conditions. To gain insight into the function of CDSP32, we applied two strategies to analyze its targets. First, using affinity chromatography with an immobilized CDSP32 active site mutant, we identified six plastidic targets of CDSP32. Three of them are involved in photosynthetic processes: ATP-ase c-subunit, Rubisco and aldolase. The three others participate in the protection against o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
137
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(143 citation statements)
references
References 66 publications
6
137
0
Order By: Relevance
“…It is possible that ACHT1 might have a transient reductive role in this time frame, during which the Calvin cycle is activated and the oxidative pentose phosphate pathway is inactivated. In case the reduction of additional Trxs, such as other ACHT family members (Dangoor et al, 2009) or the stress-induced chloroplast CDSP32 (Rey et al, 2005), is as limiting as the reduction of ACHT1, they may form a similar oxidative signaling pathway with 2-Cys Prx, which may be used to regulate other plant responses.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that ACHT1 might have a transient reductive role in this time frame, during which the Calvin cycle is activated and the oxidative pentose phosphate pathway is inactivated. In case the reduction of additional Trxs, such as other ACHT family members (Dangoor et al, 2009) or the stress-induced chloroplast CDSP32 (Rey et al, 2005), is as limiting as the reduction of ACHT1, they may form a similar oxidative signaling pathway with 2-Cys Prx, which may be used to regulate other plant responses.…”
Section: Discussionmentioning
confidence: 99%
“…These values are significantly less negative than those of the canonical plastidial Trxs f and m (approximately Ϫ360 mV at pH 7.9) (43,44) and lower than the redox midpoint potential of human Trx1 (approximately Ϫ290 mV) (45) but in the same range of those recorded for Escherichia coli Trx (46) or plastidial Trxs x and y (43,44). Interestingly, Trxs x and y are efficient reducers of the plastidial 2-Cys Prx (43) and Prx Q (44,47), respectively, two previously identified targets of CDSP32 (28,29). At pH 7.9, the redox midpoint potentials of 2-Cys Prx and Prx Q are around Ϫ370 mV (47,48), a value ϳ35 mV more negative than those of CDSP32, Trx x and Trx y, showing that efficient reduction of the disulfide bond formed in oxidized Prxs can occur only when the pool of Trxs is highly reduced.…”
Section: Table 2 Stoichiometry Of Msrb1 Reduction By Cdsp32mentioning
confidence: 99%
“…matography experiments (29). Moreover, activity assays showed that CDSP32 provides MSRB1 with electrons (16,30).…”
Section: Redox Characterization Of Wt Andmentioning
confidence: 99%
See 1 more Smart Citation
“…To answer these questions, much recent work has been devoted to large-scale searches for their putative targets. Various improved in vitro proteomic approaches [such as affinity chromatography (16)(17)(18)(19)(20)(21), labeled gel electrophoresis in which target proteins are revealed after reduction of protein extract by a TRX͞NADPH thioredoxin reductase (NTR) system (22)(23)(24), or coimmunoprecipitation (25)] suggested Ͼ100 putative TRX targets, but for which further investigations will be required for target validation regarding TRX specificity. Other methods devoted to the large-scale isolation of TRX͞target complexes established in vivo have also been developed, including affinity chromatography of TRX͞target complexes established in vivo during cell culture or the yeast͞mammalian two-hybrid methods (26)(27)(28)(29)(30)(31).…”
mentioning
confidence: 99%